Targeting the Interplay Between Autophagy and the Nrf2 Pathway in Parkinson’s Disease with Potential Therapeutic Implications - Mengru Liu; Siqi Liu; Zihan Lin; Xi Chen; Qian Jiao; Xixun Du; Hong Jiang (Biomolecules)
Parkinson’s disease (PD) is a prevalent neurodegenerative disorder marked by the progressive degeneration of midbrain dopaminergic neurons and resultant locomotor dysfunction. Despite over two centuries of recognition as a chronic disease, the exact pathogenesis of PD remains elusive. The onset and progression of PD involve multiple complex pathological processes, with dysfunctional autophagy and elevated oxidative stress serving as critical contributors. Notably, emerging research has underscored the interplay between autophagy and oxidative stress in PD pathogenesis. Given the limited efficacy of therapies targeting either autophagy dysfunction or oxidative stress, it is crucial to elucidate the intricate mechanisms governing their interplay in PD to develop more effective therapeutics. This review overviews the role of autophagy and nuclear factor erythroid 2-related factor 2 (Nrf2), a pivotal transcriptional regulator orchestrating cellular defense mechanisms against oxidative stress, and the complex interplay between these processes. By elucidating the intricate interplay between these key pathological processes in PD, this review will deepen our comprehensive understanding of the multifaceted pathological processes underlying PD and may uncover potential strategies for its prevention and treatment.